Please answer!
Drag each equation to show if it could be a correct first step to solving the equation 3(6+x)=24.

18 + 3x = 24
6 + x = 8
( 3 ⋅ 6 ) + ( 3 ⋅ x) = 24
6 + 3x = 24
3 (6 + x) = 72
18 + x = 24

Yes No Not Enough Information

Respuesta :

Answer:

Step-by-step explanation:

Initial Equation: 3(6+x)=24

18 + 3x = 24  Yes, because here you are opening up the parenthesis

6 + x = 8  Yes, because you are just dividing both sides by 3 first before opening the parenthesis

( 3 ⋅ 6 ) + ( 3 ⋅ x) = 24  Yes because this is like the first one, but just written out.

6 + 3x = 24  No because you are not distributing the 3 evenly.

3 (6 + x) = 72  No because nothing on the left side changed but the answer on the right side did.

18 + x = 24 No because it should be 18 + 3x = 24

Hope this helped!

Answer:

18 + 3x = 24 : Yes

6 + x = 8 : Yes

( 3 ⋅ 6 ) + ( 3 ⋅ x) 24 : Yes

6 + 3x = 24 : No

3 (6 + x) = 72 : No

18 + x = 24 : No

ACCESS MORE